2002
DOI: 10.1103/physrevb.65.064308
|View full text |Cite
|
Sign up to set email alerts
|

Complete spectrum of long-wavelength phonon modes inSn2P2S6

Abstract: The paper presents polarized Raman spectra of Sn 2 P 2 S 6 measured in various backscattering and nearforward and right-angle scattering geometries at Tϭ15 K. The complete sets of A TO Ј , A x Ј , A z Ј , A TO Љ , and A LO Љ mode frequencies are determined. The essential problem of symmetry assignment was solved with the help of measurements of directional dependencies of the oblique mode frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Besides, the maxima at 142, 183, and 244 cm . Note that the frequency positions of all these bands correlate with the known Sn 2 P 2 S 6 phonon spectrum [9] as well as with our earlier measurements for Sn 2 P 2 S 6 micro-and nanopowders and ceramics where features near 85, 140, 185, 245, 260, and 290 cm −1 were observed [22]. The observed features clearly confirm Sn 2 P 2 S 6 crystallite formation in the glass matrix under annealing.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Besides, the maxima at 142, 183, and 244 cm . Note that the frequency positions of all these bands correlate with the known Sn 2 P 2 S 6 phonon spectrum [9] as well as with our earlier measurements for Sn 2 P 2 S 6 micro-and nanopowders and ceramics where features near 85, 140, 185, 245, 260, and 290 cm −1 were observed [22]. The observed features clearly confirm Sn 2 P 2 S 6 crystallite formation in the glass matrix under annealing.…”
Section: Resultssupporting
confidence: 72%
“…At ambient pressure, the Sn 2 P 2 S 6 crystal undergoes a second-order structural transition from the ferroelectric phase (Pn) to the paraelectric (P2 1 /n) one at 337 K, which was thoroughly investigated by X-ray diffraction [5], dielectric studies [6], Raman scattering [7][8][9], inelastic neutron scattering [10], ultrasonic measurements [11], optical spectroscopy [12], birefringence measurements [13], Mössbauer spectroscopy [14,15], X-ray photoelectron spectroscopy [16,17], soft X-ray fluorescence spectroscopy [16], and thermal expansion studies [18]. In most cases, these studies were carried out for good quality bulk single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The final set of parameters given in table 1, was chosen by selecting the best agreement of the calculated phonon frequencies in the Brillouin zone (BZ) centre with the frequencies obtained from the RS spectra [7,12]. To make a comparison possible table 2 gives experimental data and the values of the calculated frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic properties of these crystals have been under consideration in a series of experimental works [7][8][9][10][11][12]. In [13], in particular, it has been shown that PT in Sn 2 P 2 S 6 lies in the crossover region from the "displacement" type to the "order-disorder" type.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature dependence of soft mode frequency in ferroelectric phase of Sn 2 P 2 S 6 crystals was investigated using Raman spectroscopy method in [19,20]. According to these data, the soft mode has a frequency of about 42 cm −1 at T → 0, and decreases to 27 cm −1 at T = 300 K. Using these data one can obtain the following relation [14] …”
Section: Low-temperature Limitmentioning
confidence: 99%